Die Problematik der Altersbestimmung von Plaggenböden. Möglichkeiten und Grenzen von archäologischen C14-Datierungen - Niemeier, Georg (ERDKUNDE, 1972)
Plaggen' soils are humus-rich topsoils on old arable areas, often 50 to over 100 cm thick, which originated from the application of vegetable compost mixed with mineral substances. Islands of them are to be found in the eastern Netherlands, on the lower Rhine in Germany, in the Geest and loess areas of NW Germany, further east into the Alt mark and north to the Jutland Peninsula, including the North Frisian islands. The commencement of ' Paggen' fertilisation as a precondition of continuous arable cultivation is important for the history of the cultural landscape in the areas of its distribution and has aroused the interest of geographers, pedologists and prehistorians. Determinations of age have been attempted mainly with the help of the radiocarbon method as used by Libby and with tests on prehistoric archaeological finds. These are discussed and critically compared and possible sources of error noted. Soil horizon sample cores at 10 cm intervals and their Carbon 14 dating did not give any clear results either. Archaeological material in the Ap horizon-having been admittedly subject to repeated ploughing-gives clear results only under certain conditions. Properly datable archaeological remains under the humus horizon certainly give a terminus post quern, while pots, drainage channel remnants etc within the Ap horizon or at least partially penetrating into it, give a sure terminus ante quern for the beginning of 'Plaggen' fertilisation (for example around 300 A. D. at Krefeld-Gellep). Further 'hopeful' sites are currently being investigated (e. g. on the North Frisian islands where 'Plaggen' fertilisation (for example around 300 A. D. at pre-Christian Iron Age). Diagrams and profile drawings clarify the current state of research.